Kangfuxiaoyanshuan alleviates uterine inflammation and adhesion via inhibiting NF-κB p65 and TGF-β/MMP-2 signaling pathway in pelvic inflammatory disease rats - Fan, Linyuan; Liu, Zhaohui; Zhang, Zhan; Li, Ting; Zong, Xiaonan; Bai, Huihui (Frontiers in Pharmacology, 2022)
Background and aims: Pelvic inflammatory disease (PID) is infection-induced inflammation of the female upper reproductive tract that results in high fever, ectopic pregnancy, infertility, and varying degrees of chronic pelvic pain. Recent clinical studies have shown that Kangfuxiaoyanshuan (KFXYS), a Traditional Chinese Medicine (TCM) formulation, may short the course of the disease and reduce the occurrence of PID sequelae, but its pharmacological action and potential mechanism have not been fully elucidated. Here, we aimed to investigate the therapeutic effects and mechanism of KFXYS in rats with PID. Materials and Methods: A PID rat model was constructed through endometrial mechanical injury and pathogen infection. The rectal temperature was measured during the 14-days course of treatment, and the white blood cell (WBC) count in the blood and the levels of cytokines (IFN-γ, IL-1β, IL-4, TNF-α) in the serum were evaluated by ELISA. Hematoxylin and eosin (HE) staining was performed to analyze pathological changes, and transmission electron microscopy (TEM) was used to observe ultrastructural changes. The p-p65/p65 protein expression was evaluated by western blotting and the levels of MMP-2 and TGF-β in adhesion tissues were assessed by immunohistochemistry. Results: KFXYS lowered the rectal temperature and the WBC counts in the blood in the acute stage of PID and alleviated inflammatory cell infiltration of the uterus, especially when combined with levofloxacin. KFXYS significantly decreased the levels of proinflammatory cytokines (IFN-γ, IL-1β, IL-4) and adhesion-related factors (TNF-α) and protected the ultrastructure of endometrial epithelial cells. Mechanistically, KFXYS inhibited the NF-κB activation by decreasing phosphorylation of p65, thus the alleviation of inflammation further reduced the expression of TGF-β and MMP-2, and inhibited the occurrence of uterine adhesions. Conclusion: These results revealed that KFXYS alleviated pelvic inflammation and effectively inhibits inflammation-associated adhesion, which indicated the potential role of KFXYS for treatment of PID and the prevention of PID sequelae.